A theoretical study and design of AIE-type TADF materials derived from spatially conjugated [2.2]paracyclophane - Tang, Hao; Gao, Jing; Zhang, Lan; Li, Xudong; Duan, Ying-Chen; Wen, Lili; Liu, Xingman; Su, Zhong-Min (New journal of chemistry, 2024)
A theoretical study has been conducted on a series of aggregation-induced emission (AIE) type thermally activated delayed fluorescence (TADF) materials 1-4 constructed with a [2.2]paracyclophane framework through combining quantum mechanics and molecular mechanics methods. The through-space charge transfer (TSCT) characteristics were demonstrated by the analysis of the frontier molecular orbitals and the fragmental charge transfer component between the donor and bridge, the donor and acceptor, and the bridge and acceptor. The calculated results reveal that the spatial conjugation effect leads to greater oscillator strength of some singlet excited states, and when the spin-orbit coupling (SOC) values between them and their respective neighboring triplet states are large, the corresponding intersystem crossing rate will be significantly enhanced. The TADF emission properties of the molecules were also analyzed by comparing energy gaps, reorganization energies, SOC values between the lowest singlet and triplet states in isolated and aggregated environments and the reverse intersystem crossing rates. Then, by comparing the radiative rate and the reorganization energies between S 1 and S 0 of the molecules in different environments, the enhancing effect of the aggregation environment on the luminescence efficiency of the molecules was demonstrated. Considering all the calculated parameters, we believe that molecules 2 and 4 are potential AIE-type TADF materials. AIE and TADF functional groups were combined through [2.2]paracyclophane framework in the design of AIE-type TSCT-TADF materials, and the luminescence properties were studied through quantum chemical computational methods.